A Study of Women and Polygamy in the Compilation of Islamic Law from an Egalitarian Epistemological Perspective by Asma Barlas - Amal, Muhammad Fakhri Amal; Anisah, Anisah Budiwati (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: polygamy a contentious issue in Islamic family law, is frequently perceived as a practice detrimental to women and at odds with the principles of gender justice. Objective: this study aims to analyse the position of women within polygamous practices as delineated by the Compilation of Islamic Law (KHI) in Indonesia, employing the egalitarian epistemological perspective posited by Asma Barlas. Through Barlas' approach, which advocates for an egalitarian interpretation of Islamic texts, this article seeks to investigate the extent to which the KHI affords protection and justice for women in the context of polygamy. Methods: this study utilises a qualitative method incorporating text analysis and in-depth interviews. Text analysis concentrates on articles pertaining to polygamy within the KHI, as well as relevant works by Asma Barlas. The results: the findings indicate that while the KHI has established certain conditions for men seeking to engage in polygamy, its implementation is often gender-biased and fails to adequately safeguard women's rights. Through Asma Barlas' perspective, it is demonstrated that a more egalitarian interpretation of Islamic law could yield a fairer and more inclusive understanding of the issue of polygamy. Conclusion: this study advocates for the revision of the articles concerning polygamy in the KHI, taking into account egalitarian principles and gender justice to enhance the protection of women engaged in polygamous practices in Indonesia.